(untitled) (Rehabilitation and Recreation, 2024)
The aim is to investigate the prerequisites for the use of physical rehabilitation means in athletes with cardiorespiratory system overstrain in the process of recovery. Material and methods of the research. Using Internet search databases (Scopus, Web of Science, PubMed, Google Schoolar, PEDro) the analysis and systematization of scientific and methodological literature on physical rehabilitation of athletes with cardiorespiratory system overstrain was carried out. Study results. An adequate recovery with the methodical use of rehabilitation measures is of great importance for the growth of the level of sports achievements. When choosing them the level of functional state of the body as a whole as well as the systems that are most stressed during physical activity is taken into account. The particular attention should be paid to the state of the ANS (autonomic nervous system), which ensures the most optimal course of adaptation processes in the cardiorespiratory system as well as in the athlete’s ability to maximize the use of physiological reserves and also affects the speed of recovery processes. To assess the activity of the ANS, HRV indicators were proposed, the analysis of which is a practical non-invasive method for assessing the autonomic status of the heart and makes it possible to diagnose overstrain and prevent the occurrence of pathological conditions. The HRV parameters that characterize the formation of pre-pathological conditions, namely overstrain by sympathetic and, especially, by parasympathetic types, include RMSSD, IAB, PAPR and VLF. The search for effective rehabilitation tools, that would allow us to correct functional changes in the athlete’s body occured under the influence of physical activity and that can be used directly in the conditions of the training process, focused us on the means and methods of recovery that can be used by the athlete himself – active means, or used by specialists with minimal interference with the training process against the background of nutritional optimization – passive means. Conclusions. Correction of functional changes in the body of a sportsman, which occur under the influence of physical activity, is possible due to effective means of rehabilitation, the choice of which is carried out in close cooperation with a sports medicine doctor, rehabilitation therapist and coach. When choosing physical rehabilitation means their effect on the regulatory mechanisms provided by the somatic and autonomic parts of the nervous system, as well as the possibility of using them in the “field” conditions of the training process under the guidance of a rehabilitation specialist, is taken into account.